Feasibility Assessment of Wind Energy in Poto Tano, West Sumbawa: An Integrated Economic, Environmental, and Financial Approach - Farras, Muhammad Abiyyu; Laras , Muhammad Inditiya Gegar (Ridwan Institute, 2025)
Indonesia's commitment to energy transition and climate change mitigation has intensified focus on renewable energy development, particularly wind energy as a viable alternative to fossil fuels. This research assesses the feasibility of wind energy development in Poto Tano, West Sumbawa, West Nusa Tenggara, Indonesia, through an integrated analysis of energy production, environmental benefits, and financial viability. As part of Indonesia’s commitment to diversify its energy mix and reduce greenhouse gas emissions, wind energy offers a clean, renewable alternative to fossil fuels. The research examines the potential of wind energy by utilizing RETScreen Expert software to simulate energy production based on local wind data, estimate project costs, and evaluate financial performance using metrics such as Net Present Value (NPV) and Internal Rate of Return (IRR). The environmental assessment focuses on emission reductions achieved through the displacement of fossil fuel-based electricity generation. A comprehensive cost analysis, including capital expenditure (CapEx), operational expenditure (OpEx), and maintenance costs, is presented alongside a sensitivity analysis to explore the impact of key variables on project outcomes. The research further investigates financial risks using scenario-based simulations. Results show that the region possesses consistent and strong wind resources, especially during the dry season, supporting the viability of wind power generation. The findings demonstrate that the project can contribute to Indonesia’s renewable energy targets, offer socio-economic benefits to the local community, and align with national energy and environmental policy goals. This research provides a holistic reference for future wind energy initiatives in similar geographical contexts.